Kemampuan Menulis Teks Eksplanasi Siswa Kelas XI di SMA - Verinna Syahdila Orin; Hermaliza Hermaliza (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The research method used is descriptive method with a quantitative approach. Data collection techniques used are observation techniques and test techniques The conclusion of this study is the ability to write explanatory texts for class XI students of SMA Negeri 1 Pangkalan Koto Baru, Fifty Cities District, academic year 2022/2023. The research results are based on five aspects of the research. Ability to write explanatory texts for class XI students at SMA Negeri 1 Pangkalan Koto Baru, district Fifty Cities for the 2022/2023 Academic Year of the 39 students that the author made as the research sample, judging from the average obtained by students in these five aspects, it was 71.13 and was in a fairly good category. The results of data processing showed that the lowest score achieved by students was 58 and the highest score was 88. On the genre aspect, the average score was 23.59 out of a total score of 25, on the structure aspect, the average score was 18.62 out of a total score of 25, on the technical vocabulary aspect, the average score is 10.95 out of a total score of 20, on the language rules aspect, the average score is 14.51 out of a total score of 25, and on the last aspect the writing aspect, the average score is the mean is 3.08 out of a total score of 5.